Geography: New Cartographic Techniques - Ruzaik, Fareena; Akshayan, S. (Lanka Book Depot (Pvt) Ltd, 2024)
Cartographic techniques encompass methods for creating accurate, functional maps. It begins with data collection via surveys, satellites, and GPS. This data is processed using projections mathematical transformations translating Earth’s 3D surface to 2D, such as Mercator for navigation or Robinson for minimal distortion. Symbolization employs colors, icons, and labels to depict features (rivers, roads) or thematic data (population, climate). Scale determines detail level: large-scale maps focus on smaller areas, while small-scale covers broader regions. Generalization simplifies complex data for clarity, omitting less critical details. Modern tools like GIS enable layered data analysis and dynamic visualization, while design principles color theory, typography enhance readability. Historical hand-drawn techniques contrast with today’s digital tools, yet core goals remain: clarity, accuracy, and effective communication of spatial information.
Advanced Level Cartographic techniques encompass methods for creating accurate, functional maps. It begins with data collection via surveys, satellites, and GPS.
Keywords: GIS; GNSS; MAPS; Land Survey; GPS